The Effect of Financial Technology on Financial Reporting Quality: The Mediating Role of Accounting Information Systems - Ida Bagus Putra Yogismara Yogismara (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
This research explores the impact of Financial Technology (FinTech) implementation on the quality of financial reporting, while also assessing the mediating function of Accounting Information Systems (AIS) in organizations based in Bali, Indonesia. Although FinTech adoption and financial reporting quality have been studied separately, limited research has tested AIS as a mediating mechanism across diverse organizational sectors in Bali. The study is designed to determine how the use of digital financial tools contributes to improving key aspects of financial reporting such as accuracy, reliability, timeliness, and relevance through enhanced accounting system performance. A quantitative methodology was applied, utilizing survey responses from 185 accounting and finance practitioners employed in banks, hospitality enterprises, cooperatives, and private sector organizations across Bali. Purposive sampling guided participant selection, targeting individuals active in FinTech-related financial activities. For data analysis, Structural Equation Modeling (SEM) with SmartPLS/AMOS was employed to explore direct and indirect variable relationships. FinTech adoption significantly improves financial reporting quality, and AIS partially mediates this link, showing FinTech’s direct influence plus an indirect pathway through enhanced AIS effectiveness. Organizations that integrate FinTech with efficient AIS frameworks tend to experience improved reporting accuracy, faster financial processing, and reduced errors. In conclusion, the integration of FinTech and AIS plays a crucial role in advancing financial reporting quality in Bali. Digital transformation in accounting is highlighted by the study as vital for enhancing transparency and decision-making efficiency.